The varicella-zoster virus (VZV) open reading frame 47 (ORF47) protein kinase is dispensable for viral replication and is not required for phosphorylation of ORF63 protein, the VZV homolog of herpes simplex virus ICP22. - Heineman, T C (1995)
To investigate the role of varicella-zoster virus (VZV) open reading frame 47 (ORF47) protein kinase during infection, a VZV mutant was generated in which two contiguous stop codons were introduced into ORF47, thus eliminating expression of the ORF47 kinase. ORF47 kinase was not essential for the growth of VZV in cultured cells, and the growth rate of the VZV mutant lacking ORF47 protein was indistinguishable from that of parental VZV. Nuclear extracts from cells infected with parental VZV contained several phosphorylated proteins which were not detected in extracts from cells infected with the ORF47 mutant. The herpes simplex virus type 1 (HSV-1) UL13 protein (the homolog of VZV ORF47 protein) is responsible for the posttranslational processing associated with phosphorylation of HSV-1 ICP22 (the homolog of VZV ORF63 protein). Immunoprecipitation of 32P-labeled proteins from cells infected with parental virus and those infected with ORF47 mutant virus yielded similar amounts of the VZV phosphoproteins encoded by ORF4, ORF62, ORF63, and ORF68 (VZV gE), and the electrophoretic migration of these proteins was not affected by the lack of ORF47 kinase. Therefore, while the VZV ORF47 protein is capable of phosphorylating several cellular or viral proteins, it is not required for phosphorylation of the ORF63 protein in virus-infected cells.